A Patient with Adalimumab-Induced Refractory Paradoxical Palmoplantar Pustulosis Was Successfully Treated by Ixekizumab: A Case Report - Shao XY; Xiong JX; Chen AJ; Huang K; Wang P (Dove Medical Press, 2023)
Xin-Yi Shao, Jian-Xia Xiong, Ai-Jun Chen, Kun Huang, Ping Wang Department of Dermatology, the First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People's Republic of ChinaCorrespondence: Ping Wang, Department of Dermatology, the First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi District, Chongqing, People's Republic of China, Email wang_ping@hospital.cqmu.edu.cnAbstract: Ankylosing spondylitis (AS) is a chronic immune-mediated inflammatory disorder involving the sacroiliac (SI) joints, the spine and often the hips. Biologic therapy has been shown to be efficacious in patients with AS and could improve patients' quality of life. With the increased use of tumor necrosis factor-ɑ (TNF-ɑ) inhibitors, more paradoxical reactions have been revealed. However, the treatment option for patients with AS is still a challenge when refractory paradoxical palmoplantar pustulosis appeared after the use of TNF-ɑ inhibitors. We reported the case of a 45-year-old male patient with AS treated with adalimumab treatment who developed a refractory paradoxical palmoplantar pustulosis after failure of prior secukinumab treatment. A dramatic improvement was seen in all skin and low back pain after the use of ixekizumab. We conclude that, in TNF-α inhibitors induced refractory paradoxical palmoplantar pustulosis, ixekizumab should be considered as an alternative option to choose from.Keywords: ankylosing spondylitis, refractory, paradoxical palmoplantar pustulosis, ixekizumab, biological agent